KAJIAN PENANGANAN BANJIR KALI CILIWUNG DKI JAKARTA DITINJAU DARI ASPEK HIDRO-EKONOMI (STUDI KASUS PADA RUAS CAWANG – PINTU AIR MANGGARAI) - Waluyadi, Heriantono; Jayadi, Rachmad; Legono, Djoko (Civil Engineering Forum Teknik Sipil, 2007)
Every year in a rainy season, flood inundates several areas along Ciliwung River, especially in the Cawang – Manggarai reach. Flood in this reach is caused by land use changing in upstream area and narrower the river width in the downstream area. Several planning will be implemented to reduce the flood, which are normalization with widening river, revetment and dike construction also diversion channel from Ciliwung River to East Banjir Kanal. To determine the benefit of every flood control structure the integrated and comprehensive considerations is required. The study of performance of flood management planning with hydro-economy approach that considers hydrologic, hydraulic and economic aspect is conducted in this study. The aim of this study is to determine the benefit of every flood control structure. Before determining the benefit of flood control structure, the expected annual damage must be calculated, the calculation is based on discharge-probability of exceedence curve, discharge-stage curve and stage-damage curve. The relation from above three curves will be needed for damage-probability of exceedence curve. As a result from this curve the expected annual damage and the benefit of flood control structure can be determined. The results of analysis are that the benefit of flood control structure for normalization, diversion channel with 2,5 m in width gate, diversion channel with 3,0 m in width gate and diversion channel with 3,5 m in width gate are Rp. 20 billion, Rp. 16.1 billion, Rp. 18.9 billion and Rp. 20.1 billion respectively.